The family in the contemporary world: catholic social teaching and gender = Famille dans le monde contemporain : Doctrine catholique sociale face à l’idéologie de genre = La famiglia nel mondo contemporaneo : dottrina sociale cattolica e gender - Wieczorek, Krzysztof (Philosophy & canon law, 2015)
Contemporary man confronts a dilemma. In search of his or her own identity and a model of life in human community, an individual can choose between two attitudes which exclude each other. The first one is shaped by the Catholic Social Teaching and is based on a foundation of Christian anthropology. It leads to self-identification within the framework of a double model of the human being: man and woman. Consequently, someone identified with his or her biological sex tends toward self-fulfillment in the traditional social and cultural role. The second attitude is based on the postmodern deconstruction of the category of sex. It leads to a blurred vision of one’s own sexual identity, denial of opposition and complementarity of man and woman and rejection of traditional criteria of choosing one’s way of life. This paper presents the arguments of these two attitudes and the probable consequences of choices made within the framework of both options discussed.